Pendekatan Konsep Lean Manufacturing untuk Meminimasi Waste pada Sistem Produksi (Studi Kasus PT. XYZ) - Rakhmawati Rakhmawati (Agroindustrial Technology, University of Trunojoyo Madura, 2010)
Every company wishes to provide the best possible service to their customers bydelivering their products on time, for which quality and production lead time are the key factorsthat need continuous improvements by way of adopting the right internal strategy. This researchapplies the concept of lean manufacturing to identity wastes along the value stream to find outnon added value activities. In the initial stage, Big Picture Mapping is used to describe thewhole stream entirely, than Process Activity Mapping is used to find value added, non valueadded and necessary-but-non-value added activities, whilst Quality Filter Mapping is used tofind the defects of the quality of defect type. In the last stage, Total Product Maintenance(TPM) is applied to minimize defects by means of Overall Equipment Effectiveness (OEE). TheOEE Sensitivity analysis is applied to the operating time, cycle time and defects to find out themost influential factor for the improvement of OEE. The result of this research has identifiedcycle time as the influential factor that affects the OEE value. The 10% decrease in cycle timewill improve OEE by 10,20%